Aerial autonomous catching ball using a nested second order sliding mode control*. Issue 1 (July 2017) - Ibarra-Jimenez, E.; Castillo, P.
Abstract: New applications for aerial vehicles are emerging recently. They imply the interaction with the environment with the possibility to modify it. In this paper, a control scheme to catch a ball falling using a quadcopter is conceived. The control goal is to design a controller that ensures the quick convergence in the dynamics of the quadcopter in order to catch the ball before that it touches the ground. The algorithm is based on the sliding mode approach to assure robustness and finite time convergence. The parabolic motion is studied to obtain the ball trajectory and computes the capture limit time. Simulation results verifies the well performance of the controller to catch the ball even in presence of unknown and external disturbances.